New perspective in a cross-sectional study on muscles and tendons impairments due to neuromuscular maladapted funtion found in chronic spinal cord injury - Santana, Larissa Vieira (2020)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Ceilândia, Programa de Pós-Graduação em Ciências da Reabilitação, 2020.